Rules and Commitment in Communication: An Experimental Analysis - Fréchette, Guillaume R.; Lizzeri, Alessandro; Perego, Jacopo (Econometrica, 2022)
We study the role of commitment in communication and its interactions with rules, which determine whether information is verifiable. Our framework nests models of cheap talk, information disclosure, and Bayesian persuasion. It predicts that commitment has opposite effects on information transmission under the two alternative rules. We leverage these contrasting forces to experimentally establish that subjects react to commitment in line with the main qualitative implications of the theory. Quantitatively, not all subjects behave as predicted. We show that a form of commitment blindness leads some senders to overcommunicate when information is verifiable and undercommunicate when it is not. This generates an unpredicted gap in information transmission across the two rules, suggesting a novel role for verifiable information in practice.